SISTEM DETEKSI POLUSI UDARA BERBASIS INTERNET OF THINGS - Muhammad Nur Sapi'i; Sitohang, Sunarsan (LPPM Universitas Putera Batam, 2025)
Air pollution is one of the most pressing environmental issues, especially in urban and industrial areas such as Batam City, which experiences high pollution levels due to vehicle and industrial activities. This condition significantly impacts public health, including an increased potential for respiratory diseases, asthma, and lung cancer. Therefore, an effective solution is required to monitor air quality in real-time. This research aims to develop an air pollution detection and monitoring system based on the Internet of Things (IoT) that can provide accurate and easily accessible information. The methodology employed in this study includes prototyping and literature review to understand air pollution concepts, IoT, and sensor technologies. The system is designed using MQ-2, MQ-135, and GP2Y1010AU0F sensors to detect harmful gases such as carbon monoxide, carbon dioxide, and particulate matter. The data collected by the sensors is transmitted through an IoT network and displayed on the Telegram application. This application enables users to monitor Track air quality in real-time and get alerts when the air quality changes reaches unhealthy levels. The test results show that the system effectively detects air quality changes. Notifications sent via Telegram align with measurement results displayed on the hardware. This system provides a practical and efficient solution for monitoring air quality in various locations, including industrial areas, urban settings, and public spaces. This research is expected To enhance public awareness of the hazards of air pollution and motivate action to reduce its impact.